MEMERANGI KEJAHATAN SIBER DI INDONESIA: ANALISIS REGULASI HUKUM PIDANA YANG BERLAKU DAN TANTANGANNYA - Andi Mohammad Agus Mustam (LP3M, 2023)
The rapid development of information technology and digitalization in various aspects of life has not only brought positive impacts but has also given rise to a new phenomenon called cybercrime. Cybercrime is a type of criminal activity that involves the use of digital technology and the internet. Cybercrime covers a wide range of offenses, from illegal access to computer systems, theft of data and information, the spread of malware, online fraud, defamation, to violations of personal data privacy. The surge in cybercrime cases in Indonesia calls for an urgent evaluation of the current criminal law regulations. This literature review aims to examine and analyze the laws and regulations in Indonesia related to criminal offenses in cyberspace and the extent of their effective implementation. The primary regulations that are the focus of the analysis include the Electronic Information and Transactions Law along with its amendments, as well as the latest 2019 Draft Criminal Code that contains new provisions on cybercrime.